Building strong brands - Aaker, David A. (New York : Free Press, 1996)
Examines the process of developing brand-name products, using the strategies of such companies as Saturn, General Electric, Kodak, and McDonald's to highlight successful ways of building and managing brands.
Includes bibliographical references (p. 359-366) and index.
Adult
Keywords: Brand name products -- Management; Brand name products -- Valuation -- Management; Intangible property -- Valuation -- Management; Brand name products; Brand name products -- Management